Estudo químico e histoquímico das folhas de duroia longiflora ducke (rubiaceae) - Cruz, Fabiele Souza da (Instituto Nacional de Pesquisas da Amazônia - INPA, 2017)
Duroia longiflora Ducke species belongs to Rubiaceae family, it occurs spontaneously in Brazil and it is also found in the Amazon region. Studies of the genus Duroia have demonstrated important chemical and biological potentials of their species; however, there are no previous chemical and biological studies with D. longiflora. Therefore, the objective of this work was to carry out phytochemical and biological studies with the extracts of leaves of D. longiflora, as well as to perform histochemical and anatomical studies with its leaves. The extracts were evaluated for their antioxidant, cytotoxic and antimicrobial activities, analyzed by comparative thin layer chromatography, nuclear magnetic resonance and then fractionated. For the histochemical study of the leaves, the presence of alkaloids, phenolic compounds, tannins, proteins, lipids and starch in the stained tissues were histolocalized, and in the anatomical study the leaf tissue descriptions were performed. For the biological assays, it was observed that the methanolic extracts of leaves and branches showed high toxicity against Artemia salina and high antioxidant effect. The results for the antibacterial assay were not conclusive. The extracts and the phases that presented positive activity in the biological assays were fractionated until the isolation of the compouds. It was possible to identify one biflavonoid 2,3-epoxy-5,7,3’,4’- tetrahydroxyflavan-(4-8)-epicatechin and -sitosterol from the chromatographic fractionation of the dichloromethane phase from the methanolic extract of the leaves. Other three alkaloids were isolated, but until the conclusion of this dissertation, it was not possible to carry out the structural identification.
Keywords: Anatomia foliar; Antioxidante; Toxicidade sobre artemia salina